Efeitos do custo adaptativo na germinação de biótipos de Digitaria insularis (L.) Fedde resistentes a herbicidas - Nunes, Felipe Alves (Universidade Federal de São Carlos, 2023)
Digitaria insularis poses a significant challenge in weed control due to its perennial habit, dense clumping growth, and the widespread presence of herbicide-resistant biotypes. Our research investigates whether single or multiple herbicide resistance biotypes of D. insularis experience fitness costs, specifically affecting their germination. To determine the resistance factor, a dose-response curve was employed using glyphosate and haloxyfop-P-methyl herbicides separately in a completely randomized design (CRD) with four replicates per dose (nine doses total). Shoot dry mass was measured at 100 days after herbicide application (DAA), with control assessments performed at 14, 28, and 42 DAA. Subsequently, a separate CRD experiment examined the germination rate as a function of temperature and photoperiod for each biotype. This factorial scheme tested six temperatures across three biotypes (susceptible and two resistant types) under three light exposure periods (0, 8, and 12 hours). Germination percentage and
Effects of fitness costs on herbicide-resistant Digitaria insularis (L.) Fedde germination
Keywords: Glifosato; Haloxifope-P-metílico; Capim-amargoso; Resistência; Glyphosate; Haloxyfop-P-methyl; Sourgrass; Resistance; CIENCIAS AGRARIAS::AGRONOMIA::FITOSSANIDADE